A comparison of the performance of submerged and detached artificial headlands in a beach nourishment project. (1st July 2018) - Pan, Y.; Kuang, C.P.; Chen, Y.P.; Yin, S.; Yang, Y.B.; Yang, Y.X.; Zhang, J.B.; Qiu, R.F.; Zhang, Y.
Abstract: Submerged Artificial Headland (SAH) and Detached Artificial Headland (DAH) are two types of modified artificial headland to provide better water exchange at slightly weakening beach protection effect compared to Traditional Artificial Headland (TAH). In this paper a numerical investigation is conducted on performances of SAH and DAH in a beach nourishment project. The beach protection and water exchange are considered respectively. A shoreline model and a constituent transport model are set up to simulate the post-project shoreline change and water exchange. The results of shoreline changed model show that both the SAH and DAH have good performance in protecting the beach behind them, while in SAH case the shoreline has a smoother shape. The effects of eroding and silting characteristics of the beach on the performance of SAH and DAH are also discussed. The SAH and DAH have similar performance of reducing the flushing time and improving the water exchange in the area behind the artificial headlands compared to TAH. The effect of tidal condition on the flushing time is also discussed. It is suggested that both SAH and DAH are feasible and effective measures to strengthen the water exchange at the cost of an acceptable loss of beach protection. Highlights: Submerged Artificial Headland (SAH) and Detached Artificial Headland (DAH) are studied. Numerically investigate the performances of SAH and DAH in a beach nourishment. Both SAH and DAH have good performances in protecting the beach behind them. SAH and DAH have similar performances in reducing the flushing time compared to Traditional Artificial Headland (TAH). SAH and DAH are effective in balance the water exchange and beach protection.